Kajian Corporate Governance dan Likuiditas terhadap Kinerja Keuangan Pada Sektor Property dan Real Estate - Louw, Febriana (MABIS, 2011)
The development started from the perspective of corporate governance agency theory, where the agency theory, which acts as the principal owner of the company hand over authority to the agent. With the separation between ownership and management of the company will bring up the difference between agent and principal interests that could pose a potential conflict of interest. Corporate governance appears to control the behavior and resolve conflicts between parties within the company. Research on corporate governance on performance, has become a common focus, but the results of previous studies showed inconsistent results. To reconcile differences in the results of the study, carried out similar studies with different objects. The study was done in order to find empirical evidence of the influence of the elements in the application of good corporate governance on the performance of property companies and real estate sector in Indonesia. Population used in this study is a property companies and real estate sector registered in Indonesia Stock Exchange (BEI), while the sample is a company during the period 2007-2010. Sampling was done by purposive sampling method. Hypothesis testing is done by multiple regression analysis. From the results of testing the hypothesis, suggesting that the influence of corporate governance by institutional ownership ,independent commissioners, audit committee and the level of liquidity has a negative relationship and do not significantly affect the companys financial performance. The results also indicate that the size of the board of directors has a positive and significant impact on performance .In general, the results of this study indicate that the companys property and real estate sector in Indonesia has begin to implement good corporate governance in an effort to improve company performance and to protect the interests of the principal.